Association of nutrition knowledge, practice, supplement use, and nutrient intake with strength performance among Taekwondo players in Nepal - Sunuwar, Dev Ram; Singh, Devendra Raj; Bohara, Man Prasad; Shrestha, Vintuna; Karki, Kshitij; Pradhan, Pranil Man Singh (Frontiers in Nutrition, 2022)
Background: Optimum dietary intake and adequate nutritional knowledge have been recognized as the key factors that play a critical role in improving the athlete's health and nutrition status. This study aimed to measure the association of nutritional knowledge, practice, supplement use, and nutrient intake with strength performance among Taekwondo players. Methods: Between August 2019 and January 2020, a cross-sectional study was conducted among 293 Taekwondo students in Kathmandu Metropolitan City (mean age, 18 years; 63.1% male, 36.9% female). Face-to-face interviews were conducted using semi-structured questionnaires. Anthropometric measures, nutritional intake, nutrition knowledge, and practice were recorded. The handgrip strength was measured using a handgrip dynamometer as a proxy for strength performance. Univariate and bivariate analyses were used to find out the association between predictor and outcome variables. Results: More than half of the participants had poor nutrition knowledge [54.3% (159/293)], and poor nutrition practice [55.3% (162/293)] scores. Daily mean energy, carbohydrate, protein and fat intake were 48.0 g.kg-1.d-1, 8.6 g.kg-1.d-1, 1.6 g.kg-1.d-1, and 1.5 g.kg-1.d-1, respectively among Taekwondo players. Daily total energy and carbohydrate intake were 48.2 kcal.kg-1.d-1 and 8.7 g.kg-1.d-1, respectively among male players, which is higher than female players. However, daily protein and fat intake were higher in female players (1.7 g.kg-1.d-1 and 1.6 g.kg-1.d-1, respectively). Both calcium (375.3 mg) and iron (9 mg) intake among Taekwondo players were significantly lower than current sports nutrition guidelines. Nutritional knowledge score (r=0.117), height (r=0.538), weight (r=0.651), body mass index (r=0.347), fat (r=0.075), and energy (r=0.127) intake showed significant positive correlation with handgrip strength of athletes. The strength performance was positively associated with training hours per day (β=0.41, 95% CI: 0.09-0.91), body mass index (β=0.35, 95% CI: 0.09-0.61), nutrition knowledge score (β=0.13, 95% CI: 0.01-0.25), and energy intake (β=0.13, 95% CI: 0.12-0.14). Conclusions: The nutritional knowledge and nutrient intake both were suboptimal among Taekwondo athletes. Height, weight, body mass index, nutritional knowledge, energy, and fat intake showed a positive correlation with strength performance. Future studies can build on the premise of this study to identify the robust relationship between nutritional knowledge, practice, different supplement use, and nutrient intake among other athletes too.